Analytical characterization of the palette and painting techniques of Jorge Afonso, the great 16th century Master of Lisbon painting workshop - Antunes, Vanessa (2018)
In this work, a study on a set of paintings from the most significant altarpiece assigned to Master Jorge Afonso (c. 1470–1540) painting workshop is presented. This altarpiece is composed by fourteen paintings made to the church of Convento de Jesus, in Setúbal, Portugal, and was made circa 1517–19/1530, according to art-history. This set of paintings is compared to one of the other most important Portuguese altarpieces from the 16th century: the panels of the Round Church of the Convento de Cristo, in Tomar, made circa 1510–1515. The aim of this study is to characterize the wooden support, pigments, ground layers materials and technique used in Jorge Afonso workshop by means of complementary analyses. A dendrochronological approach was made in order to corroborate (or not) the historical date initially assigned. Infrared photography (IRP) and reflectography (IRR) allowed the study of the underdrawing technique and macro photography (MP) was used to recognize overlapping layers technique. Cross-sections from the paintings were examined by optical microscopy (OM), and analyzed by μ-X-ray diffraction (μ-XRD), Energy Dispersive X-ray Fluorescence spectroscopy (EDXRF), Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM-EDS), micro-Raman spectroscopy (μ-Raman), micro-Fourier Transform Infrared spectroscopy (μ-FTIR), Pyrolysis Gas Chromatography Mass Spectrometry (py-GC/MS). The characterization of the palette and ground layers and the study of the overlapping of paint layers brought a new insight of the adopted painting techniques by the most important group of painters working in Portugal in the 16th century - the Lisbon workshop, leaded by Master Jorge Afonso.